Obesity and female fertility: a primary care perspective. Issue 3 (1st July 2009) - Wilkes, Scott; Murdoch, Alison
Abstract : Infertility affects approximately one in six couples during their lifetime. Obesity affects approximately half of the general population and is thus a common problem among the fertile population. Obese women have a higher prevalence of infertility compared with their lean counterparts. The majority of women with an ovulatory disorder contributing to their infertility have polycystic ovary syndrome (PCOS) and a significant proportion of women with PCOS are obese. Ovulation disorders and obesity-associated infertility represent a group of infertile couples that are relatively simple to treat. Maternal morbidity, mortality and fetal anomalies are increased with obesity and the success of assisted reproductive technology (ART) treatments is significantly reduced for obese women. Body mass index (BMI) treatment limits for ART throughout the UK vary. The mainstay for treatment is weight loss, which improves both natural fertility and conception rates with ART. The most cost-effective treatment strategy for obese infertile women is weight reduction with a hypo-caloric diet. Assisted reproduction is preferable in women with a BMI of 30 kg/m 2 or less and weight loss strategies should be employed within primary care to achieve that goal prior to referral.